PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN MOTIF DAN PELATIHAN BATIK BERBASIS RAGAM HIAS SITUS CANDI SINGOSARI - Aditya Nugroho Widiadi; Yuliati Yuliati; Najib Jauhari; Ronal Ridhoi (Universitas Negeri Malang, 2023)
COMMUNITY EMPOWERMENT THROUGH THE DEVELOPMENT OF BATIK MOTIFS AND TRAINING BASED ON THE DECORATIVE VARIETIES OF THE SINGOSARI TEMPLE SITECandirenggo village has extraordinary tourism potential to be developed as a source of community empowerment. One of these potentials is the existence of Singosari Temple. Unfortunately, the existence of Singosari Temple cannot be utilized optimally because it only relies on tourist visits to the temple and surrounding sites. Even though the Singosari Temple site has so many ornamental motifs on some parts of the temple as well as on some artifactual relics located in the temple courtyard. This article aims to explain the development of batik motifs by taking inspiration from the variety of decorations that exist in Singosari Temple and several statues around it. Then, the motif was offered to the people of Candirenggo village through batik training activities. The method of developing batik motifs was through identification studies at the Singosari Temple site. Then continued with focus group discussion activities with archeologist and local community leaders. The result of this development is a form of batik motif named SinghÄsana Padma. In the final stage, a community empowerment program is carried out through batik training activities in Singosari village which can be used for iconic merchandise for Singosari Temple tourism.Kelurahan Candirenggo memiliki potensi wisata yang luar biasa untuk bisa dikembangkan sebagai sumber-sumber pemberdayaan masyarakat. Salah satu potensi tersebut adalah keberadaan Candi Singosari. Namun sayangnya, keberadaan Candi Singosari belum bisa dimanfaatkan secara optimal karena hanya mengandalkan kunjungan wisatawan ke candi dan situs sekitarnya. Padahal situs Candi Singosari memiliki kekayaan motif ragam hias pada beberapa bagian dinding candi maupun pada beberapa peninggalan artefaktual yang terletak di halaman candi. Artikel ini bertujuan untuk memaparkan pengembangan motif batik dengan mengambil inspirasi dari ragam hias yang ada pada Candi Singosari dan beberapa arca di sekitarnya. Untuk kemudian, motif tersebut ditawarkan kepada masyarakat Kelurahan Candirenggo melalui kegiatan pelatihan membatik. Metode pengembangan motif batik ini melalui studi identifikasi di situs Candi Singosari, lalu dilanjutkan dengan kegiatan focus group discussion dengan para arkeolog dan tokoh masyarakat setempat. Hasil dari pengembangan ini adalah bentuk motif batik yang diberi nama SinghÄsana Padma. Pada tahap akhir dilaksanakan pemberdayaan masyarakat melalui kegiatan pelatihan membatik di Kelurahan Singosari yang dapat dimanfaatkan untuk merchandise ikonik untuk wisata Candi Singosari.